E Pluribus Unum? Constructing a Typology of Contemporary Dutch Evangelicals - Vermeer, Paul (Journal for the scientific study of religion, 2024)
Against the background of the assumed polymorphous character of evangelicalism as a trans-denominational movement, this article aims to construct a typology of Dutch evangelicals and, subsequently, to test whether this religious typology also manifests sociodemographic differences. Two research questions are addressed: Which types can be distinguished among contemporary Dutch evangelicals on the basis of their core religious convictions and religious orientations? and To what extent do these types also display sociodemographic differences? Analyzing survey data on more than 1100 Dutch evangelicals using latent class analysis reveals five types of evangelicals: Proclaiming Orthodox, Engaged Orthodox, Spiritual Orthodox, Seeking Orthodox, and Questing Liberals. These five types basically seem to represent an orthodox-liberal continuum and mainly differ in terms of gender, age, income, education, and marital status.